An amphibious drone for aerial, surface, and underwater assets and environmental remote monitoring to support the sustainability of unmanned offshore converted platform - Cacace, Jonathan; Lippiello, Vincenzo; Paduano, Gianmarco; Pierro, Fabio (GEOmedia, 2023)
The PlaCE project aims at investigating technologies and solutions for the ecosustainable reuse of offshore platforms at the end of their production phase. In this context, robotic mobile solutions that allow in a versatile way to monitor the activities by acquiring environmental data and parameters in the entire area of interest have been explored. This paper presents a solution achieved through the development of the proof-of-concept of a robotic technology concerning a hybrid Autonomous / Remotely Piloted Aircraft System (A/RPAS), hereinafter referred to as Amphibious Drone, operating in complete autonomy and having the platform as an operational base. The Amphibious Drone is developed to cover the entire area of interest surrounding the platform being converted, with the ability to carry the measuring instruments and probes in aerial overflight for monitoring the sea surface and the surface structures as well as ditching to deploy a sensors-equipped probe for measuring underwater parameters along the water column. A wide range of probes and instruments have been integrated into the system such as multispectral camera, Photosynthetically Active Radiation (PAR) probes, Conductivity-Temperature-Depth (CTD) probes, etc. for the analysis of oceanographic and biological parameters of the marine ecosystem. The management of the Amphibious Drone, as regards the shelter between missions, battery recharging, data exchange, required reconfigurations and missions scheduling is carried out from a specially designed Docking Station. The PlaCE project is co-funded by the European Union within the projects “PON Ricerca e Innovazione 2014-2020”.